2021
DOI: 10.35848/1882-0786/ac1de5
|View full text |Cite
|
Sign up to set email alerts
|

Coherent detection stochastic resonance assisted biomagnetometer for measuring magnetocardiography at room temperature

Abstract: A method of magnetocardiography (MCG) measurement using an overdamped bistable model based stochastic resonance (SR) technique for advancing biomagnetic sensors is proposed. To determine the system parameters for SR, an evolutionary algorithm combined with the coherent detection (CD) method is applied. We acquire and process an animal MCG at room temperature, detected by a commercially available optically pumped magnetometer. A comparison with a lowpass filter and the traditional CD method verified the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In future work, we plan to perform experiments to collect the BP and ICP data simultaneously and study a regression model that leverages brain BIOZ to estimate BP and ICP simultaneously. Finally, recent studies have introduced the utilization of magnetic sensors, such as magnetocardiography, for the contactless monitoring of BIOZ [45] and cardiac signal [46]. BrainZ-BP monitoring system can also expand to using magnetic sensors for contactless BP estimation.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…In future work, we plan to perform experiments to collect the BP and ICP data simultaneously and study a regression model that leverages brain BIOZ to estimate BP and ICP simultaneously. Finally, recent studies have introduced the utilization of magnetic sensors, such as magnetocardiography, for the contactless monitoring of BIOZ [45] and cardiac signal [46]. BrainZ-BP monitoring system can also expand to using magnetic sensors for contactless BP estimation.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…The biocompatibility and chemical inertness of diamond make it widely used in biology and medicine. 7,8) Extremely low-frequency magnetic field has great value in biological research, which can directly exert influence biological tissue, such as some researchers have confirmed that the use of extremely low-frequency magnetic fields can inhibit the growth of cancer cells without causing lymphocyte necrosis; 9,10) on the other hand, by detecting the extremely low-frequency magnetic field generation by the organism itself to identify the biological state, it has been applied in some experiments, such as in the biological magnetic field research of the human heart, [11][12][13] it is found that the cardiac magnetic field is an extremely lowfrequency magnetic field, at the same time, influenced by the changes in cardiac physiological characteristics, which is used in the diagnosis of heart disease or potential disease. In addition, diamond is also used in battery testing, 14) IC imaging, 15,16) current sensing, [17][18][19] and other fields.…”
Section: Introductionmentioning
confidence: 99%